A Study of Accounting Learning Achievements Using Emotional Intelligence and Learning Behavior - Tiyas Yuniarti; Purweni Widhianningrum; Nur Wahyuning Sulistyowati (Universitas PGRI Madiun, 2020)
ABSTRACTThe study aims to examine the influence of emotional intelligence and learning behavior towards accounting learning achievements. The population in this study is a student of education accounting study program year 2014. Total samples obtained some 71 students with a purposive sampling technique. The data analysis method used is multiple regression. The results proved that among emotional intelligence and learning behavior, only emotional intelligence had a positive effect on accounting learning achievements. These results indicate that students with good self-resilience can empathize and cooperate with others. This intelligence can support their success in implementing accounting concepts when they enter the workforce and various aspects of life.ABSTRAKPenelitian ini bertujuan untuk menguji pengaruh kecerdasan emosional dan perilaku belajar terhadap prestasi belajar akuntansi. Populasi dalam penelitian ini adalah mahasiswa program studi akuntansi pendidikan tahun 2014. Total sampel diperoleh sejumlah 71 siswa dengan teknik purposive sampling. Metode analisis data yang digunakan adalah regresi berganda. Hasilnya membuktikan bahwa di antara kecerdasan emosi dan perilaku belajar, hanya kecerdasan emosi yang memiliki efek positif pada prestasi belajar akuntansi. Hasil ini menunjukkan bahwa siswa dengan ketahanan diri yang baik dapat berempati dan bekerja sama dengan orang lain. Kecerdasan ini dapat mendukung keberhasilan mereka dalam menerapkan konsep akuntansi ketika mereka memasuki dunia kerja dan berbagai aspek kehidupan.